“Too small to be targeted:” Perceived Cybersecurity Vulnerabilities of Small-Scale U.S. Farmers - Lulu Rodriguez; Kristine Micheletti; Shuyang Qu; Fally Masambuka-Kanchewa (Journal of International Agricultural and Extension Education, 2026)
As agriculture becomes increasingly digitalized, farms face rising exposure to cyberthreats that jeopardize data security, productivity, and business continuity. This study examined small-scale crop and livestock producers’ perceptions of cybersecurity risks, their experiences with cyberattacks, and their information sources across 12 U.S. Midwest states. Guided by the Social Amplification of Risk Framework (SARF), a mixed-mode survey design was used, combining online and mail questionnaires distributed to 14,000 small farms between November 2023 and April 2024. Findings revealed that while most farmers were moderately familiar with cybersecurity concepts and recognized the importance of protective action, many underestimated their likelihood of being targeted. Farmers expressed the greatest concern over personal identity theft and computer viruses but were less aware of broader operational vulnerabilities. The majority practiced basic protective behaviors such as anti-malware installation and data backup, yet fewer implemented advanced measures like encryption or multifactor authentication. Media, friends, and relatives were the most frequently cited information sources, while formal channels such as Extension services were seldom used. Results underscore a critical need for cybersecurity literacy programs tailored to rural communities and smallholder operations. The study extends SARF by showing how interpersonal communication and perceived relevance shape risk awareness and protective behavior in the agricultural sector. The insights also hold international value, offering a model for strengthening digital resilience in global farming systems.
Keywords: Cybersecurity in agriculture; cyber threats in farming; smallholder farmers’ perceived cyber vulnerabilities; cybersecurity protective behaviors of small-scale farmers; farmers’ cybersecurity information sources